KEJAHATAN DAN CAMPUR TANGAN TUHAN (Sebuah Tinjauan Teodesi dan Teologi Islam) - syafieh, syafieh (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2019)
This article discusses God 's omniscience and interference in the theological and Islamic’s theological perspectives. Theodical problem that centered on causality and the administration of God since the days of Greece God presented as a defendant. Berger uses theodicy concept to give meaning to the suffering experienced by humans in the world, while simultaneously promising happiness "in the world there". In this connection religion is clearly a force of alienation. Crime and suffering as a privacy are always present in reality and life. While Islamic’s theological reject the theodetic concept, according to Muttahharri, that on the plains of phenomena there is no "real evil" or "true goodness", while on plain noumena there is only one essence, namely goodness, because the substance of evil is truly pure nothingness.